Infiltrant resins in odontopediatric patients: an integrative review (Research, Society and Development, 2020)
Objective: To analyze the efficacy of infiltrating resins in the treatment of dental caries in pediatric dental patients. Methodology: This is an integrative review, in which the descriptors "Resin", "White spot lesion" and "Pediatric Dentistry" were used to search the studies in the SciELO and PubMed databases. Articles available in full and free of charge in the languages Portuguese and/or English, published and indexed in these databases in the last ten years (2009-2019) were included. Results: Throughout the search trajectory, the titles of three hundred and seventy-seven articles were read and 12 articles were pre-selected after reading the abstracts. After excluding articles that did not portray the theme and duplicated in both databases, 10 articles were included. Conclusion: There is still insufficient scientific evidence to prove a better efficacy of infiltrating resins in pediatric dental patients, compared to other noninvasive techniques for treating dental caries, reinforcing the need for further studies and well-defined methodologies. Thus, fluoride remains the gold standard for use in pediatric dentistry due to its low cost and proven efficacy in the treatment of initial dental caries.